Distributions of non‐native and native plants are not determined by the same environmental factors - Bart Steen; Antoine Adde; Martin A. Schlaepfer; Antoine Guisan; Luigi Maiorano (Ecological Solutions and Evidence)
Abstract Global environmental change will cause shifts in species communities, with non‐native species likely replacing native ones at an unprecedented rate. This will have consequences for biodiversity and ecosystem services, in addition to the ecological and economic damage caused by those non‐native species that are invasive. Understanding general patterns driving distributions of native and non‐native species is therefore vital, but no study has compared yet whether environmental variables that correlate with a species' presence differ between the two groups other than at local scale and often with very limited sample size. In this study, we focus on 141 native and non‐native congeneric plant species pairs at the scale of Switzerland. In the framework of correlative species distribution models, we used newly developed methods for efficient automated selection of a parsimonious number of predictor environmental variables to determine which ones, out of a large candidate set in eight classes, have the strongest explanatory power for both species groups. Our results indicated that variables influence the two groups in significantly different ways. Climate was by far the strongest determinant of both native and non‐native species distributions, although it had significantly more explanatory power in native species models. Models for non‐native species were significantly more influenced by anthropogenic factors, land use variables and forest cover. The presence of non‐native species was also associated with habitats with a significantly lower mean naturality value than native species. These findings provide novel empirical evidence for the different environmental factors driving native and non‐native plants' distributions and guidance for non‐native species management. Practical implications: species distribution models are an increasingly frequently advised tool for conservation management and our results provide guidelines on which covariates should be specifically considered to assess the habitat suitability of non‐native versus native species. The distributions of the former group of species are particularly important to research, as, in time, they may turn invasive. In addition, areas close to infrastructure should be scanned regularly for incipient colonizations by non‐native species, especially in as yet uninvaded areas, such as high mountains.